Paradigmatic Conflict of Law on Narcotics and Legislative Synchronization with the New Indonesia Criminal Code - Ikawati, Linda; Putra, Rengga Kusuma; Nugraha, Satriya; Saraya, Sitta; Mardani, Retno Eko (Kertha Patrika, 2025)
This study analyzes the paradigmatic dilemma of Indonesia’s narcotics law: the necessity of strict prosecution against transnational syndicates versus the humanitarian crisis of prison overcrowding caused by the incarceration of addicts. Law Number 35 of 2009 concerning Narcotics embodies a philosophical dualism (retribution vs. rehabilitation), yet its implementation is dominated by a punitive orientation. The purpose of this research is to analyze the philosophical tension within Law 35/2009 and project the implications of its legislative synchronization with the restorative principles in the new Criminal Code (Law 1/2023). The method used is normative juridical with a prescriptive character, utilizing statutory, conceptual, and comparative approaches. The results conclude that the new Criminal Code risks significant failure in resolving the capacity crisis due to restrictions on alternative sanctions for crimes carrying penalties of over five years, which covers the majority of Narcotics cases. The codification attempt also potentially weakens the prosecution of transnational crimes due to the incomplete adoption of special investigation techniques. The primary recommendation is a firm legislative synchronization that separates jurisdiction: the new Criminal Code as lex generalis for minor users, and the Narcotics Law as a strengthened lex specialis to target dealers, supported by the implementation of factual decriminalization based on public health.
Keywords: Criminal dynamics; 2023 criminal code; Narcotics; Legal revolution; Narcotics law